2017
DOI: 10.1155/2017/8027307
|View full text |Cite
|
Sign up to set email alerts
|

An Anatomical Study of Maxillary-Zygomatic Complex Using Three-Dimensional Computerized Tomography-Based Zygomatic Implantation

Abstract: Objective To obtain anatomical data of maxillary-zygomatic complex based on simulating the zygomatic implantation using cadaver heads and three-dimensional computerized tomography (3D-CT). Methods Simulating zygomatic implantation was performed using seven cadaver heads and 3D-CT images from forty-eight adults. After measuring the maxillary-zygomatic complex, we analyzed the position between the implantation path and the maxillary sinus cavity as well as the distance between the implantation path and the zygom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Similar values have been reported in other studies. Uchida et al [ 21 ] and Xu et al [ 25 ] reported average lengths of 50.2 ± 4.13 mm (range 44.3–54.3 mm) and 58.15 ± 7.50 mm (range 36.46–72.35 mm), respectively. If anterior emergence was contemplated at the level of the canines/first premolars, the implant length required to attain the external cortical area of malar bone was 58.32 ± 7.44 mm.…”
Section: Discussionmentioning
confidence: 99%
“…Similar values have been reported in other studies. Uchida et al [ 21 ] and Xu et al [ 25 ] reported average lengths of 50.2 ± 4.13 mm (range 44.3–54.3 mm) and 58.15 ± 7.50 mm (range 36.46–72.35 mm), respectively. If anterior emergence was contemplated at the level of the canines/first premolars, the implant length required to attain the external cortical area of malar bone was 58.32 ± 7.44 mm.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Tzerbos et al, 15 reported that some complications may be associated with limited intraoperative visibility, as well as the complexity of anatomical structures, which can lead to a more demanding surgery. Similarly, Xu et al, 16 noted that traditional methods for measuring anatomical variables are not adequate, due to the difficulty in obtaining structural details of the underlying tissues. They stressed on the importance of collecting all possible information to determine the best route of implant insertion that should be considered to avoid injuries to the eyeball, frontal wall of the maxillary sinus, or infratemporal fossa.…”
Section: Discussionmentioning
confidence: 99%
“…Cone beam CT imaging was performed on a Morita Accuitomo Scanner (J. Morita, Accuitomo 170, Kyoto, Japan) with the following imaging parameters: Case 2: image acquisition voxel size 0.080 × 0.080 × 0.080 mm 3 , reconstructed slice thickness 0.960 mm, slice interval 0.480. Case 4: image acquisition voxel size 0.250 × 0.250 × 0.250 mm 3 , reconstructed slice thickness 1.0 mm, slice interval 0.5. CBCT images were visualized, using the OnDemand 3DApp Software (CyberMed, Seoul, Korea).…”
Section: Methodsmentioning
confidence: 99%
“…Currently, the conventional volume rendering technique (VRT) is the most common method used in imaging with well-known benefits for the detection, interpretation, diagnosis, and for treatment planning of dentomaxillofacial lesions. [1][2][3] Cinematic rendering (CR) is a relative recently introduced postprocessing technique, which is based on an advanced 3D algorithm. It allows for a more photorealistic visualization of structures and lesions compared to standard VRT postprocessing.…”
mentioning
confidence: 99%